Choosing an Animal Model for the Study of Functional Dyspepsia. (12th February 2018) - Ye, Yang; Wang, Xue-Rui; Zheng, Yang; Yang, Jing-Wen; Yang, Na-Na; Shi, Guang-Xia; Liu, Cun-Zhi
Abstract : Functional dyspepsia (FD) is a common functional gastrointestinal disorder with pain or discomfort in the upper abdomen as the main characteristic. The prevalence of FD worldwide varies between 5% and 11%. This condition adversely affects attendance and productivity in the workplace. Emerging evidence is beginning to unravel the pathophysiologies of FD, and new data on treatment are helping to guide evidence-based practice. In order to better understand the pathophysiologies of FD and explore better treatment options, various kinds of animal models of FD have been developed. However, it is unclear which of these models most closely mimic the human disease. This review provides a comprehensive overview of the currently available animal models of FD in relationship to the clinical features of the disease. The rationales, methods, merits, and disadvantages for modelling specific symptoms of FD are discussed in detail.